Ultramorphological characteristics of unknown larva of Phloeonomus punctipennis Thomson, 1867 (Coleoptera; Staphylinidae; Omaliinae): an obligate saproxylic species: notes on chaetotaxy and ecological preferences - Staniec, Bernard; Wagner, Grzegorz K.; Pietrykowska-Tudruj, Ewa (Zootaxa, 2016)
The aim of the study was to describe the morphological ultrastructure, including chaetotaxy, of the previously unknown early (L1) and late (L2-3) larval instars of Phloeonomus punctipennis. The diagnostic larval characters for the genus Phloeonomus are proposed for the first time. Morphological differences between L1 and L3 refer only to the proportion of length of individual parts of antennae and legs as well as length proportion of urogomphi and their subapical setae. The chaetotaxy of the mature larvae of P. punctipennis and Dalotia coriaria, as a model of aleocharine larvae, is compared. Despite some identified differences, the chaetotaxic system proposed previously for Aleocharinae is successfully applied to the larva of P. punctipennis. It may most probably be also useful for larvae of other Omaliinae species. Also, information on geographical distribution and the ecological preferences of this species is provided, as is the information on accompanying insects.